Effect of V-shaped Ribs on Internal Cooling of Gas Turbine Blades - Harishkumar Kamat; Satish B. Shenoy; Chandrakant R Kini (Journal of Engineering and Technological Sciences, 2017)
Thermal efficiency and power output of gas turbines increase with increasing turbine rotor inlet temperature. The rotor inlet temperatures in most gas turbines are far higher than the melting point of the blade material. Hence the turbine blades need to be cooled. In this work, simulations were carried out with the leading edge of gas turbine blade being internally cooled by coolant passages with V-shaped ribs at angles of 30°, 45° or 60° and at three aspect ratios (1:1, 1:2 and 2:3). The trailing edge of the blade was cooled by cylindrical and triangular pin-fin perforations in staggered and inline arrangements. Numerical analyses were carried out for each configuration of the cooling passages. The best cooling passages for leading edge and trailing edge were deduced by comparing the results of these analyses. It was found that using V-shaped ribs and fins induces a swirling flow, which in turn increases the velocity gradient and hence produces an improvement in heat transfer. The results show that under real time flow conditions, the application of V-shaped ribs and pin-fin perforations is a very promising technique for improving blade life.